Dissociated Oxygen Consumption and Carbon Dioxide Production in the Post–Cardiac Arrest Rat: A Novel Metabolic Phenotype. Issue 13 (3rd July 2018) - Shinozaki, Koichiro; Becker, Lance B.; Saeki, Kota; Kim, Junhwan; Yin, Tai; Da, Tong; Lampe, Joshua W.
Abstract : Background: The concept that resuscitation from cardiac arrest (CA) results in a metabolic injury is broadly accepted, yet patients never receive this diagnosis. We sought to find evidence of metabolic injuries after CA by measuring O2 consumption and CO2 production (VCO2 ) in a rodent model. In addition, we tested the effect of inspired 100% O2 on the metabolism. Methods and Results: Rats were anesthetized and randomized into 3 groups: resuscitation from 10‐minute asphyxia with inhaled 100% O2 (CA–fraction of inspired O2 [FIO2 ] 1.0), with 30% O2 (CA‐FIO2 0.3), and sham with 30% O2 (sham‐FIO2 0.3). Animals were resuscitated with manual cardiopulmonary resuscitation. The volume of extracted O2 (VO2 ) and VCO2 were measured for a 2‐hour period after resuscitation. The respiratory quotient (RQ) was RQ=VCO2 /VO2 . VCO2 was elevated in CA‐FIO2 1.0 and CA‐FIO2 0.3 when compared with sham‐FIO2 0.3 in minutes 5 to 40 after resuscitation (CA‐FIO2 1.0: 16.7±2.2, P <0.01; CA‐FIO2 0.3: 17.4±1.4, P <0.01; versus sham‐FIO2 0.3: 13.6±1.1 mL/kg per minute), and then returned to normal. VO2 in CA‐FIO2 1.0 and CA‐FIO2 0.3 increased gradually and was significantly higher than sham‐FIO2 0.3 2 hours after resuscitation (CA‐FIO2 1.0: 28.7±6.7, P <0.01; CA‐FIO2 0.3: 24.4±2.3, P <0.01; versus sham‐FIO2 0.3: 15.8±2.4 mL/kg per minute). The RQ of CA animals persistently decreased (CA‐FIO2 1.0: 0.54±0.12 versus CA‐FIO2 0.3: 0.68±0.05 versus sham‐FIO2 0.3: 0.93±0.11, P <0.01 overall). Conclusions: CA altered cellular metabolism resulting in increased VO2 with normal VCO2 . Normal VCO2 suggests that the postresuscitation Krebs cycle is operating at a presumably healthy rate. Increased VO2 in the face of normal VCO2 suggests a significant alteration in O2 utilization in postresuscitation. Several RQ values fell well outside the normally cited range of 0.7 to 1.0. Higher FIO2 may increase VO2, leading to even lower RQ values.